2017
DOI: 10.1038/ncomms13958
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid CB2 receptor ligand profiling reveals biased signalling and off-target activity

Abstract: The cannabinoid CB2 receptor (CB2R) represents a promising therapeutic target for various forms of tissue injury and inflammatory diseases. Although numerous compounds have been developed and widely used to target CB2R, their selectivity, molecular mode of action and pharmacokinetic properties have been poorly characterized. Here we report the most extensive characterization of the molecular pharmacology of the most widely used CB2R ligands to date. In a collaborative effort between multiple academic and indus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
397
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 291 publications
(427 citation statements)
references
References 64 publications
21
397
8
1
Order By: Relevance
“…These studies and others indicate that the CB 2 receptor is up-regulated in response to immune cell activation and inflammation (Klein, 2005; Stella, 2010). More recently, CB 2 receptor expression has been reported in the healthy CNS (Van Sickle et al, 2005), although its presence in adult native brain tissue remains somewhat controversial (Atwood & Mackie, 2010; Soethoudt et al, 2017). …”
Section: Distributionmentioning
confidence: 99%
“…These studies and others indicate that the CB 2 receptor is up-regulated in response to immune cell activation and inflammation (Klein, 2005; Stella, 2010). More recently, CB 2 receptor expression has been reported in the healthy CNS (Van Sickle et al, 2005), although its presence in adult native brain tissue remains somewhat controversial (Atwood & Mackie, 2010; Soethoudt et al, 2017). …”
Section: Distributionmentioning
confidence: 99%
“…CB2 is activated by compounds such AM1241, JWH-133, HU-910, and HU-308 [26]; in addition, there are compounds without special selectivity for either cannabinoid receptor, such as HU-210, CP 55,940, and R-(+)-WIN 55,212-2. On the other hand, there are CB1 antagonists such as SR141716A and AM251; and CB2 antagonists such as SR144528 and AM630 [14,26] (Fig. 1).…”
Section: Cb1 and Cb2 And Physiological Regulationmentioning
confidence: 99%
“…31 We found no effect of the CB2R agonist, JWH-133, on PTZ-induced seizures (Figure 4). [46][47][48] The doses of JWH-133 and SR144528 used in this study were selected because they had been previously shown to elicit effects in the brain in other models of neurological disorders. [29][30][31][32][33] We selected JWH-133 and SR144528 for our studies because they are highly potent and CB2R-specific, F I G U R E 6 Deletion of CB2Rs does not worsen flurothyl-induced seizures in Scn1a RH/+ mutant mice.…”
Section: Discussionmentioning
confidence: 99%